Equine coital exanthema : New approaches to minimise the negative impact on the equine industry - Vissani, Maria Aldana (Wiley, 2024)
Equine coital exanthema (ECE), caused by Equid alphaherpesvirus 3 (EHV-3), is a highly contagious, venereally transmitted mucocutaneous disease, characterised by the formation of papules, vesicles, pustules and ulcers on the external genital organs of mares and stallions. The infection is endemic worldwide, and the virus is transmitted mainly through direct contact during sexual intercourse and by contaminated instruments during reproductive manoeuvres in breeding facilities. The only known biological reservoir of EHV-3 is the latently infected horse; it is well-known that, as for other herpesviral infections, periods of reactivation from latency, with production and shedding of infectious virus, are the source of infection for other comingling susceptible animals. Episodes of reactivation and shedding, either with or without clinical manifestation, and together with variable levels of serum antibodies, have been observed. Although the disease is relatively benign and does not result in systemic illness, infertility or abortion, it does have a negative impact on the equine industry, as it forces to temporarily withdraw affected animals, consequently disrupting mating activities in breeding enterprises. Thus, outbreaks of ECE continue to be a major problem for the equine industry, mostly in those facilities with heavily scheduled breeding calendars during reproductive seasons. For affected stallions, such disruptions may translate into significant end-of-season decreases in the mare-book size. Similarly, affected mares may miss breeding opportunities. In artificial insemination and embryo transfer centres, affected mares may be reluctant to be inspected, inseminated or transferred, with the consequent loss of opportunities to become pregnant. In both scenarios (natural mating or artificial insemination), delayed foaling dates or reduced pregnancy rates may occur in mares that miss breeding opportunities because of the disease. In the interest of reducing the negative impact of EHV-3 infections on breeding centres, advances have been made during the last years as to diagnostic methodologies, treatment and prevention.